ABO and Rh Blood Group Distribution and Its Association with Hemoglobin Levels in Pregnant Women: A Study from Peshawar District: Blood Group Distribution in Pregnant Women - Jamil, Nadra; Sarwar, Nayab; Alam, Shaista; Khalid, Maida; Khan, Sara Jamil; Malik, Saira Nasr (Pakistan Journal of Health Sciences, 2024)
Anemia was a significant global health issue, leading to preterm birth, low weight at birth, and fetal malformations in pregnancy. Determination of blood group distribution and their relationship with anemia was essential for improving anemia management in pregnancy. Objective: To assess the distribution of the ABO blood group and Rh type of pregnant women and its relationship with the concentration of hemoglobin. Methods: A descriptive cross-sectional design study was conducted at a primary healthcare center in Peshawar from 1st January 2023 to 31st December 2023, enrolling 1049 pregnant women attending antenatal care. ABO and Rh typing were determined, and Hb levels were assayed to assess the presence of anemia in the participants. The data were analyzed using SPSS version 26.0. To examine the relationship between various blood group types and anemia, ANOVA and correlation analysis were employed. Results: B-type was the most prevalent blood group among the participants, about 358 (34.1%), followed by O 295 (28.1%), A 279 (26.6%), and AB about 117 (11.2%). The majority of participants, 972 (92.7%), were Rh-positive. Anemia was prevalent in 878 (83.7%) of participants, with 639 (60.9%) having mild anemia. Linear regression analysis indicated no significant impact of ABO blood group or Rh factor on hemoglobin levels (p > 0.05). Conclusions: In the current study, B-type was the most prevalent blood group among pregnant women, differing from previous reports of blood group O. However, no significant association was observed between blood group types and anemia, suggesting that other factors might play a more significant role in the prevalence of anemia.